Understanding the effect of soil particle size on corrosion behavior of natural gas pipeline via modelling and corrosion micromorphology. (October 2017) - He, Bin; Han, Pengju; Hou, Lifeng; Zhang, Decheng; Bai, Xiaohong
Abstract: The effect of particle size on the electrochemical corrosion behavior of natural gas pipeline steel in a 1.5 wt% NaCl sandy soil corrosive environment was investigated by standard quartz sand. A mathematical model of gas/liquid/solid three-phase boundary (TPB) zone and the soil particle size was developed, and then the theoretical calculation indicated that a critical particle size corresponded to 1.2 mm radius. The laboratory experiments indicated that the corrosion rate of natural gas pipeline steel increased with decreasing soil particle size to < 1.0 mm and was mainly determined by a cathodic reaction. Whereas the corrosion rate of pipeline steel increased with increasing soil particle size exceeding 1.0 mm and the dominant reaction was metal dissolution in the bulk zone and the corrosion rate was determined by anodic reaction. The modelling result is in good agreement with experimental data. Highlights: Effect of particle size on corrosion behavior of × 70 steel has been investigated. A model considering the size effects in soil environment was proposed. A critical particle size equal to 1.2 mm was obtained. Corrosion rate of × 70 steel in soil environment depends on particle size. The corrosion scale was characterised using XRD and SEM/EDS.